Genotype and phenotype relationships in neurodevelopmental disorders - Vrcelj, K (2017)
NeuroDevelopmental Disorders (NDDs) are a group of heterogeneous neuropsychiatric conditions, encompassing Developmental Delay (DD), Intellectual Disability (ID), Autism Spectrum Disorder (ASD) and Gilles de la Tourette Syndrome (GTS). NDDs often involve a life-long need of supportive services and represent a major economic and societal burden in Europe and the United States. Hitherto, no safe and effective treatment strategies are available, underpinning the urgency of deciphering their elusive aetiology. NDDs have a strong genetic component. Accordingly, the mechanistic understanding of disease involves (1) the description of mutational landscapes, (2) the molecular and cellular of characterisation of genetic variants and (3) their integration at circuit and system levels. In this thesis, we tackled these theoretical underpinnings to provide insights into the genetics of NDDs and the onset of associated clinical abnormalities. Firstly, aiming to shape the genetic architecture of GTS, a condition characterised by the presence of motor and vocal tics, we undertook a whole-genome CNV study of a cohort of Danish GTS cases and healthy controls. Using statistical and functional genomics approaches, we proposed novel potential candidate genes and implicated the disruption of early neurodevelopmental and late synaptic processes in the aetiology of GTS. Secondly, to elucidate the vast phenotypic heterogeneity of NDDs, we conducted a systematic investigation of genotype and phenotype relationships in DD, ID and ASD. Taking advantage of extensive phenotypic and genetic data available for DD/ID and ASD patients, we grouped individuals based on their functional rare CNV and gene disruptions but did not to identify distinguishing clinical archetypes. Instead, we showed converging molecular perturbations underlie the onset of globally more similar clinical presentations and investigated the role of common variants in modulating their expressivity. Lastly, we established the relevance of mouse models in the study of human disease. By applying comprehensive genomics approaches to over 1,000 mouse neuroanatomical knockouts, we implicated early neurodevelopmental and adult synaptic processes in the aetiology of ID and brain malformations. Furthermore, we showed that functionally converging genetic disturbances translate at the phenotypic level and proposed novel candidate ID genes.